Shaping the structure and properties of HyTemp using polyethylene glycol diglycidyl ether cross-linkers - Dossi, Eleftheria; Mutele-Nkuna, Khuthadzo Lourate; Wilkinson, Peter; Kister, Guillaume; Patrick, Hugh; Khalili, Mohammad Hakim; Hawi, Sara (Wiley, 2024)
Novel elastomers are made by reaction of hydroxyl-terminated polyacrylic ester (HyTemp) with polyethylene glycol (PEG, number of ethylene glycol units 1, 3, 6, 9) based cross-linkers. The influence of the cross-linker length, the HyTemp/cross-linker (w/w) ratio and the cross-linking accelerator trifluoromethanesulfonate scandium salt (ScTFMS) on the structure and the properties of the materials are studied. The cross-linker length has not influence on the glass transition (Tg) of the products because of the presence of the flexible PEG units that cancels out the cross-linking effect associated to a shift to higher Tg. A two-domain structure is seen by the presence of a dual Tg in samples cured with ScTFMS. Mathematical analysis of the modulated differential scanning calorimetry curves offers for the first time the possibility to identify/confirm structural differences in complex three-dimensional polymeric structures. Scanning electron microscopy and swelling experiments in ethyl acetate respectively reveal an increase in the pore size (1.13 to 5.48 nm) and in the absorption ability of the elastomers cured with different types and quantities of PEG cross-linker. The new elastomeric materials are exhibiting a rubbery state over a wide temperature range and absorptivity for the potential recovery of pollutants in soil and/or water.
Keywords: curing; diglycidyl ethers; elastomer; modulated differential scanning calorimetry; swelling